Strategic Analysis of Food Raw Material Procurement Using TOWS Matrix : JEL Classification: M11, L66, L83, M31, Q13 - Zuliansyah Zuliansyah; Margriet Puspa Dewi; Darminiyanti Darminiyanti (Journal La Bisecoman, 2026)
This study aims to analyze the internal and external factors affecting the procurement system of food raw materials at Bale Lazara Resto Palembang and formulate appropriate procurement strategies using the TOWS Matrix approach. This research employs a qualitative descriptive method, utilizing data collection techniques including in-depth interviews with key informants (General Manager, Head Chef, and purchasing staff), direct observation, and documentation studies of internal company records. Data analysis was conducted through the stages of data condensation, data display, and conclusion drawing, complemented by quantitative assessments using IFAS and EFAS matrices. The findings reveal that Bale Lazara Resto has a weak internal position with a total IFAS score of 1.85, characterized by weaknesses in manual stock management systems, low human resource efficiency, and non-technical interference in kitchen operations. Conversely, the external position is strong with an EFAS score of 2.85, driven by opportunities from the growing culinary lifestyle trends, digital delivery platform expansion, and social media promotion potential. The strategic position falls within Quadrant III of the Cartesian diagram (Turnaround Strategy) and Cell IX of the IE Matrix (Harvest or Divest), indicating that the company faces significant internal constraints despite favorable market opportunities. The TOWS Matrix analysis prioritizes WO strategies, focusing on digitalizing stock management systems through POS implementation, standardizing kitchen SOPs, and enhancing workforce professionalism to capture opportunities in the digital food delivery market. This research contributes practical strategic recommendations for culinary businesses facing similar operational challenges and theoretical insights into the application of TOWS Matrix in the food and beverage industry context.